2022
DOI: 10.3389/fcvm.2022.849143
|View full text |Cite
|
Sign up to set email alerts
|

Pacing Characteristics of His Bundle Pacing vs. Left Bundle Branch Pacing: A Systematic Review and Meta-Analysis

Abstract: BackgroundHis bundle pacing (HBP) is a physiological pacing strategy, which aims to capture the His bundle-Purkinje system and synchronously activate the ventricles. Left bundle branch pacing (LBBP) is a newly discovered physiological pacing technique similar to HBP. We conducted this meta-analysis to compare the pacing parameters and clinical results between HBP and LBBP.MethodsWe systematically retrieved studies using the PubMed, Embase database, and Cochrane Library. Mean difference (MD) and relative risk (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 33 publications
(59 reference statements)
2
28
0
5
Order By: Relevance
“…BiV pacing is an established treatment option for patients undergoing the “pace and ablate” strategy [ 6 , 7 , 8 ]. Recently reported high acute success rates of HBP and LBBP made these two modalities a potential alternative to BiV [ 24 ]. In the line with these reports, the present study demonstrated successful permanent CSP pacemaker implantation combined with AVNA in all enrolled patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BiV pacing is an established treatment option for patients undergoing the “pace and ablate” strategy [ 6 , 7 , 8 ]. Recently reported high acute success rates of HBP and LBBP made these two modalities a potential alternative to BiV [ 24 ]. In the line with these reports, the present study demonstrated successful permanent CSP pacemaker implantation combined with AVNA in all enrolled patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, LBBP appeared to result in shorter fluoroscopy time duration, less complications during AVNA and lower pacing thresholds compared to HBP group and BiV group. Namely, LBBP lead is screwed deep within the LV septum and close to the myocardial tissue, thus stimulating not only the specialized conduction system but also the deep myocardium of the interventricular septum [ 24 ]. In accordance with previous published literature, pacing thresholds in our study remained stable during short-term follow-up in both CSP groups [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This success rate is similar to that reported in other studies 10 . Other studies have found a higher implant success rate with LBBAP as compared to HBP 11 . Second, this success rate is likely easily reproducible as the implant technique does not require additional or specialized training, only a long delivery sheath and some familiarity with the mechanism to fix the 3830 lead to the interventricular septum.…”
Section: Figurementioning
confidence: 99%
“…10 Other studies have found a higher implant success rate with LBBAP as compared to HBP. 11 Second, this success rate is likely easily reproducible as the implant technique does not require additional or specialized training, only a long delivery sheath and some familiarity with the mechanism to fix the 3830 lead to the interventricular septum. With preliminary data suggesting improved outcomes compared to traditional RV septal pacing 12 and the relative ease of procedural proficiency, it would seem that this technique could rapidly become the gold standard for pacemaker implantation.…”
mentioning
confidence: 94%